Tingkat Kepuasan Pasien terhadap Pelayanan Kefarmasian di RSUD Dr. Murjani Sampit: The Level of Patient Satisfaction to Pharmaceutical Service in Dr. Murjani Hospital Sampit - Susi Novaryatiin; Syahrida Dian Ardhany; Siti Aliyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Good pharmaceutical services are directly oriented services in the drug use process aimed at ensuring the safety, effectiveness, and rationality of drug use by applying science and function in patient care. Consumer satisfaction is the response of customer or service user for each service provided. The purpose of this study was to determine the level of patient satisfaction with pharmaceutical service in RSUD Dr. Murjani Sampit. This study was conducted using the descriptive method. The level of satisfaction was measured by the five dimensions of service quality and was analyzed using percentage and Likert scale. The results showed the average percentage of interpretation score of 68% which means included in the category of satisfaction.